Unusual Root Canal Morphology of the Maxillary Second Molar: A Case Report - Neslihan Şımşek; Ali Keleş; Elçin Tekın Bulut (Case Reports in Dentistry)
Introduction. This clinical case report presents the successful endodontic treatment of a maxillary second molar that has a mandibular molar-like anatomy with no palatal root and with each of its roots containing two separate root canals. Cone-beam computed tomography (CBCT) was used to confirm this unusual anatomy. Methods. A 34-year-old male patient was referred to the Department of Endodontics at Inonu University’s Faculty of Dentistry because of severe pain in his right maxillary second molar. Clinical and radiographic examinations identified unusual roots and root canals anatomy, and CBCT was planned in order to understand the nature of these variations. Cleaning and shaping procedures were performed using the crown down technique with Sybron Endo (Glendora, CA, USA) rotary instruments, and endodontic treatment was completed with gutta-percha cones and AH Plus resin sealers using the cold lateral compaction technique. Conclusions. The maxillary second molar exhibits aberrations and variations in terms of the numbers and configurations of its roots and root canals, and CBCT can be a useful imaging technique in endodontics.